G-Group E-Shopping With Drive-Through (eWay) : Effective Drive-Through Operation For eWay - Guan, Huoi Ying (2010)
Customers purchase grocery from retail stores to fulfill living needs and requirements. The current purchase model in Malaysia requires customers to walk in to the store to perform purchase activity, predominantly referred to as traditional purchase store. Pelanggan membeli barangan keperluan melalui pasaraya untuk memenuhi keperluan harian. Model pembelian di negara Malaysia memerlukan pelanggan memasuki pasaraya untuk membeli barangan keperluan, iaitu pembelian secara tradisi.